Strategi Pemerintah Desa Untuk Meningkatkan Partisipasi Masyarakat dalam Rangka Pembangunan Desa (Studi pada Desa Kemamang Kecamatan Balen Kabupaten Bojonegoro) - Lailiani, Bella Arinta (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Village Government Strategies to Increase Community Participation in the Framework of Rural Development. Community participation in Desa Kemamang appears in the implementation of the policy that is related to the development of the village, but in general the participation of people in Kemamang Village is less than the maximum. The purpose of this study is to know and describe the strategy of village government to increase community participation in the framework of village development in Kemamang Village Balen District Bojonegoro District. Data analysis in this research is done qualitative descriptive data analysis technique and to determine strategy done with SWOT analysis. The results show that based on SWOT matrix and SWOT analysis in Diagram, it is known that the right strategy to be applied by Kemamang Village Government of Balen District Bojonegoro Regency in increasing community participation in rural development is S-O strategy. The strategy is to build a shared commitment with the community and utilize the funds so that the realization of village infrastructure development can be completed soon. Â  Keyword :Strategy of Village Government, Community Participation, Rural Development